1998
DOI: 10.1002/jlb.63.2.169
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF instillation into rat lungs mediates neutrophil recruitment, pulmonary edema, and hypoxia

Abstract: Activated neutrophils (PMN) have been implicated in the pathogenesis of adult respiratory distress syndrome (ARDS). Granulocyte colonystimulating factor (G-CSF) is essential for PMN production and activation of PMN functions. We have recently shown that levels of G-CSF mRNA in a rat model of hemorrhagic shock correlated with severity of shock, PMN infiltration, pulmonary edema, and hypoxia. To determine whether increased tissue levels of G-CSF contribute to PMN recruitment and PMN-mediated injury, we instilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…The hypothesis that lung injury could result from locally increased levels of G-CSF and subsequent neutrophil recruitment and activation was later confirmed by intratracheal injection of G-CSF; BAL fluid and lung biopsies revealed marked edema of the interstitium and alveoli. 5 Iijima et al 6 found significant increases in the rheological activity of leukocytes and serum levels of granulocyte elastase in patients receiving G-CSF as compared to those in untreated subjects. Our patient developed an acute, systemic inflammatory reaction which started during leukapheresis and culminated in serosal inflammation and effusion, hypoxemia, shock, edema, neurologic changes and hepatic injury.…”
Section: Discussionmentioning
confidence: 98%
“…The hypothesis that lung injury could result from locally increased levels of G-CSF and subsequent neutrophil recruitment and activation was later confirmed by intratracheal injection of G-CSF; BAL fluid and lung biopsies revealed marked edema of the interstitium and alveoli. 5 Iijima et al 6 found significant increases in the rheological activity of leukocytes and serum levels of granulocyte elastase in patients receiving G-CSF as compared to those in untreated subjects. Our patient developed an acute, systemic inflammatory reaction which started during leukapheresis and culminated in serosal inflammation and effusion, hypoxemia, shock, edema, neurologic changes and hepatic injury.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, experimental models show that intravenous instillation of recombinant G-CSF can exacerbate pre-existing acute lung injury [31±33]. Furthermore, it has recently been reported that G-CSF alone can induce acute lung injury when introduced directly into the lungs of rats [34]. Doses of 300±3,000 ng recombinant human G-CSF introduced intratracheally caused hypoxia, marked pulmonary oedema and pulmonary neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Hierholzer et al have shown that installing G-CSF into the lungs of rats by intratracheal injection resulted in recruitment of neutrophils, lung injury, and impaired pulmonary function [44].…”
Section: Biotherapeutic Agentsmentioning
confidence: 99%